The didactic significance of non-traditional teaching methods in developing students’ monologic speech competence - Salisheva, Zilola Ismailovna (The Lingua Spectrum, 2026)
This article examines the role and significance of non-traditional lesson formats, particularly museum lessons, excursion-based lessons, and theatre lessons, in developing students’ monologic speech competence. In modern education, one of the key tasks is to develop students’ independent thinking and their ability to express ideas freely and coherently. From this perspective, non-traditional teaching methods based on practical and creative approaches serve as effective tools compared to traditional lessons. The article analyzes that museum lessons allow students to directly engage with historical and cultural sources and express their impressions orally; excursion lessons promote observation in real environments and presentation of impressions in monologic speech; and theatre lessons enhance students’ creative thinking by helping them develop expressive and logically structured speech through role-playing activities. According to the research results, these non-traditional lesson formats increase students’ speech activity, expand their vocabulary, and strengthen their ability to present ideas consistently. Moreover, such approaches make the learning process more engaging and effective. The teacher acts as an organizer and facilitator in this process. In conclusion, museum lessons, excursion lessons, and theatre lessons are important pedagogical tools for developing monologic speech competence, and their systematic implementation in education leads to higher learning outcomes.